2009
DOI: 10.1089/adt.2009.0203
|View full text |Cite
|
Sign up to set email alerts
|

Conformational mAb as a Tool for Integrin Ligand Discovery

Abstract: alpha(4)beta(1)-Integrin (very late antigen-4 (VLA-4)) mediates cell adhesion to cell surface ligands (VCAM-1). Binding of VLA-4 to VCAM-1 initiates rolling and firm adhesion of leukocytes to vascular endothelium followed by the extravasation into the tissue. VLA-4-dependent adhesion plays a key role in controlling leukocyte adhesive events. Small molecules that bind to the integrin ligand-binding site and block its interaction with natural ligands represent promising candidates for treatment of several diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…As shown previously, the EC50 for mAb binding is similar to the ligand dissociation constant (K d ) determined using other methods [54]. We observed that the EC50s for LIBS antibody binding for CORM-2 treated samples were larger than for the vehicle treated controls by ~2 fold for resting cells, and ~3 fold for FPR activated cells (Figure 6).…”
Section: Resultssupporting
confidence: 85%
“…As shown previously, the EC50 for mAb binding is similar to the ligand dissociation constant (K d ) determined using other methods [54]. We observed that the EC50s for LIBS antibody binding for CORM-2 treated samples were larger than for the vehicle treated controls by ~2 fold for resting cells, and ~3 fold for FPR activated cells (Figure 6).…”
Section: Resultssupporting
confidence: 85%
“…This approach has been verified for multiple VLA-4 ligands. The EC50s for βl-integrin LIBS mAbs (HUTS-21) binding determined in the mAb-binding experiments were identical to K i s, determined in the competition assay with fluorescent VLA-4 ligand (37). This novel approach can be used for determination of ligand-binding affinities for unlabeled ligands, as well as for previously unknown integrin ligands.…”
Section: Mabs and Integrin Conformationsupporting
confidence: 52%
“…Such conformational changes were reported for the α4β1, αLβ2 integrins and have been validated through exposure of the activation-dependent antibody epitopes and x-ray crystallography to visualize resting and extended integrins 10 12 …”
Section: Introductionmentioning
confidence: 72%